The use of Sn-impregnated activated carbon for the removal of CO in PSA system - S. E. Iyuke,; A. B. Mohamad,; W. R. W. Daud, (2001)
Inevitable increase of carbon monoxide (CO) in the atmosphere as a result of its emission from process gases,has remained a threat to the world ecosystem. It is then expedient to develop technologies to either eliminate or at least reduce the concentration of co to a minimum bearable level in order to protect the world from its pollution. Consequently, Sn-Activated carbon adsorbent was developed and itsCOsorption and thermodynamic properties were studied and then applied in PSA system. Activated carbon was impregnated with 34.57% SnCH2.2H20 salt to improve its adsorptive interaction with CO. It was observed that the amount of CO adsorbed was almost equal to that desorbed which could imply that the adsorption of CO on the prepared adsorbents seems to be reversible. Further exploitation of the impregnated activated carbon in pressure swing adsorption (PSA) experiments showed that adsorption of carbon monoxide was higher with the impregnated carbon than in the pure